2022
DOI: 10.1101/2022.06.27.497727
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Newcastle disease burden in Nepal and efficacy of Tablet I-2 vaccine in commercial and backyard poultry production

Abstract: Poultry (Gallus domesticus) farming plays an important role as an income generating enterprise in a developing country like Nepal, contributing more than 4% to the national GDP. It is also one of the major sources of protein for growing population. Newcastle Disease (ND) is a major poultry disease affecting both commercial and backyard poultry production worldwide. There were more than 90 reported cases of ND outbreaks in Nepal in 2018, with over 74,986 birds being affected. ND might be responsible for over 7%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Moreover, ND I-2 vaccine was shown to induce protective levels of antibodies up to 90 days post vaccination in village chickens [24]. A recent study showed that thermostable I-2 NDV vaccine in tablet formulation is effective against NDV, including a virulent 2021 outbreak strain with 85% efficacy [10]. These findings, together with ours, highlight the importance of continuous use of NDV vaccination in the farms.…”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“…Moreover, ND I-2 vaccine was shown to induce protective levels of antibodies up to 90 days post vaccination in village chickens [24]. A recent study showed that thermostable I-2 NDV vaccine in tablet formulation is effective against NDV, including a virulent 2021 outbreak strain with 85% efficacy [10]. These findings, together with ours, highlight the importance of continuous use of NDV vaccination in the farms.…”
Section: Discussionsupporting
confidence: 60%
“…Vaccination together with stringent biosecurity measures are practiced worldwide to prevent NDV infection in the farm [15]. Most of the commercial poultry farms in Nepal also practice regular vaccination against NDV [10]. Despite vaccination, ND outbreaks are common each year leading to a huge economic loss [1,3].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations